Grain size control in the fabrication of large single-crystal bilayer graphene structures1. Issue 6 (14th February 2015) - Gan, Lin; Zhang, Haijing; Wu, Ruizhe; Zhang, Qicheng; Ou, Xuewu; Ding, Yao; Sheng, Ping; Luo, Zhengtang
<x xml:space="preserve">Abstract</x> Single-crystalline bilayer graphene with the largest reported size of up to 540 μm in diameter has been synthesized by an improved APCVD method.